(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
It has been collect five fishes of Mastacembelus mastacembelus in the days 25\7 ,30\7 and 5\8 of the year 2018 from the fishermen that fishing from Al-mashrooa river one Km from the floodgate which connect it with Euphrates River at Al-Musaib region and after dissection and examine it have been isolate the parasite Centrocestus formosanus phase Excysts metacercaria from the gill and it’s isolation for the first time then it regarded as new hosts in Iraq.